How young people live love: Gender relations in the private sphere - Arteaga Béjar, Yanet (2001)
In Peru, over the last few years, there have been many changes regarding society in general; Among them, the access of women to the public sphere and to education stands out. Although it is true that approximately in the 1960s many "liberal" ideas had been introduced regarding female behavior in couples (including both its affective and sexual manifestations), these ideas and practices have become more widespread in the generation of men. the nineties, with modernity and equality, extended above all in urban spaces, in which the idea of ​​equality and individuation becomes more generalized.